Learning Disabilities and Frontal Lobe Damage - J Gordon Millichap (Pediatric Neurology Briefs, 1991)
Two adult patients age 31 and 26 years who suffered bilateral prefrontal damage early in life and who subsequently presented with severe aberrant behavior, are reported from the Division of Behavioral Neurology and Neuroscience of the Harvard Neurology Department and Beth Israel Hospital, Boston, MA.